2015
DOI: 10.1097/yic.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin variations during risperidone therapy in a sample of drug-naive children and adolescents

Abstract: The aim of this prospective observational study was to investigate the variations of serum prolactin hormone (PRL) in a sample of 34 drug-naive patients (mean age 13 years) who started risperidone therapy assuming that several factors may favor the increase in serum PRL. Serum PRL and hyperprolactinemia clinical signs were examined at baseline (T0) and after almost 3 months of treatment (T1). We considered sex, pubertal status, risperidone dosage, psychiatric diagnosis, and any personal/family history of autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…We did not identify an association between PRS and age; however, a negative association was identified between PRS and age at onset. Similarly, it has been demonstrated that the mean plasma prolactin level was increased in early-onset schizophrenia spectrum psychosis patients compared with no-early-onset patients [32]. Another finding of this study is that the risperidone dose was positively associated with the severity of PRS, which is consistent with the previous study.…”
Section: Discussionsupporting
confidence: 91%
“…We did not identify an association between PRS and age; however, a negative association was identified between PRS and age at onset. Similarly, it has been demonstrated that the mean plasma prolactin level was increased in early-onset schizophrenia spectrum psychosis patients compared with no-early-onset patients [32]. Another finding of this study is that the risperidone dose was positively associated with the severity of PRS, which is consistent with the previous study.…”
Section: Discussionsupporting
confidence: 91%
“…Thirdly, this study did not have any data of describing serum prolactin level of the patients before receiving risperidone treatment. To account for this limitation, age-and genderappropriate reference ranges [16] were used to define hyperprolactinaemia. Lastly, this study did not comment on whether patients had symptoms (such as amenorrhoea or others mentioned above) as a result of the increase; it only reported that in the laboratory, prolactin levels were increased in the patients' blood.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [16] revealed that the increase in serum prolactin may be linked to other factors, such as the drug and its dosage, sex, pubertal stage and psychiatric disease. Our previous study [15] revealed an association between prolactin level and risperidone dosage.…”
mentioning
confidence: 99%
See 2 more Smart Citations